Restorative justice in context : international practice and directions - Weitekamp, Elmar G. M.; Kerner, Hans-Jürgen (Willan, 2003)
This book brings together a selection of papers originally presented and discussed at the fourth international restorative justice conference, held at the University of Tbingen. The contributors include many of the leading authorities in the burgeoning field of restorative justice, and they provide a comprehensive review of developing international practice and directions, and the context in which restorative justice practices are developing. Restorative Justice in Context moves beyond a focus on restorative justice for juveniles to a broader concern with the application of restorative justic.